The perceptions of II MBBS students toward flipped classroom as an active method of learning - Tejeswini Vaddatti; B Chaitra; I V Renuka; Ramya Potti (Wolters Kluwer Medknow Publications, 2022)
Introduction: With the advent of competency-based medical education, self-directed learning and student-centric approach have been emphasized. The flipped classroom (FC) is a learning design which encourages active involvement of students. Hence, this study was conducted to assess the effectiveness and perceptions of FC among II MBBS students. Materials and Methods: This was an interventional study done on II MBBS students. The study material on a topic was provided to all participants 1 week before interaction and assessment sessions. The perception of students was assessed by a standard validated questionnaire with Likert scale and open-ended questions. The knowledge gained was assessed by a total of 10 multiple-choice questions, 5 each from topics covered by FC and traditional method and scores analyses by unpaired t -test among high and low achievers and between two methods. Results: A total of 103 students were included in the study. In this study majority of students felt that flipped classroom was more engaging, motivating and increased communication. This method was also flexible they could go through the course according to their own pace and helped in improving learning. The overall rating of FC was 60.83%. The mean scores in topics delivered by FC (2.05 ± 1.17) were higher than that of traditional didactic lecture (1.46 ± 1.02) and P = 0.0001 was statistically significant and also among high achievers (P = 0.0001). Conclusions: This study concludes that majority of students perceived FC as an effective strategy for learning and test scores of students were higher with FC than with traditional lecture and also in high achievers compared to low achievers.